1982
DOI: 10.1115/1.3138303
|View full text |Cite
|
Sign up to set email alerts
|

Properties and an Anisotropic Model of Cancellous Bone From the Proximal Tibial Epiphysis

Abstract: An investigation has been made of the source and magnitude of anisotropic material properties of cancellous bone in the proximal epiphysis of the human tibia. Results are reported for stiffness measurements made in three orthogonal directions on 21 cubes of cancellous bone before testing to failure along one of the three principal axes. The structure is approximately transversely isotropic. Strength and stiffness are linear with area fraction for loading along the isotropic axis. Strength is proportional to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(133 citation statements)
references
References 0 publications
2
130
0
1
Order By: Relevance
“…Trabecular bone has an aligned composite porous micro structure and is both inhomogeneous and anisotropic (Townsend et al, 1975;Williams and Lewis, 1982;Hodgskinson and Currey, 1990). Solely on-axis uniaxial and confined compression testing was performed for BTB therefore the anisotropy of the trabecular specimens could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Trabecular bone has an aligned composite porous micro structure and is both inhomogeneous and anisotropic (Townsend et al, 1975;Williams and Lewis, 1982;Hodgskinson and Currey, 1990). Solely on-axis uniaxial and confined compression testing was performed for BTB therefore the anisotropy of the trabecular specimens could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Pugh et al (1973) modeled the subchondral trabecular bone as a collection of structural plates and concluded that bending and buckling were major modes of deformation of the trabeculae. Williams and Lewis (1982) modeled the exact structure of a twodimensional section of trabecular bone with plane strain finite elements to predict the apparent transversely isotropic elastic constants. They concluded that the modulus of trabecular bone tissue was much less than that of cortical bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Gibson, 1985;Williams and Lewis, 1982;Pugh et al, 1973), generally assume that the effect of the apparent stress, {Q,,,} (or strain, {E,~~}) on the microstructure can be represented by self equilibrated anti-periodic traction or displacement boundary conditions. These approaches then solve for the total tissue strain using the standard form of the variational equilibrium equation (shown here for the traction boundary condition):…”
Section: Introductionmentioning
confidence: 99%
“…However, natural auxetic materials do exist, examples being single crystals of arsenic (35) and cadmium (36), α-cristobalite (37), and many cubic elemental metals (38). In addition, some biological materials have been found to be auxetic, including certain forms of skin, for example, cat skin (39), salamander skin (40), and cow teat skin (41), and load-bearing cancellous bone from human shins (42). Furthermore, the mechanisms of auxetic materials depend on either their microstructure or their geometrical structure and on the deformation mechanisms of these structures when they deform.…”
Section: Introductionmentioning
confidence: 99%